Graphene oxide membrane with high separation efficiency and high ion selectivity, and preparation method and application thereof
By isotropic stretching and steam treatment of graphene oxide film, combined with low-temperature reduction technology, the problem of irregular structural failure and assembly of graphene oxide film during separation is solved, efficient separation and high ion selectivity are achieved, and the stability and separation performance of the film are improved.
Patent Information
- Application Number
- CN202510148243.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-11
AI Technical Summary
During the separation process, existing graphene oxide films are susceptible to the insertion of water molecules of GO nanosheets, resulting in interlayer structure failure and reducing separation performance. At the same time, there are irregular morphology of the sheet layer and low assembly order during the assembly process, which affects the transmission efficiency and selectivity of ions.
By isotropic stretching and steam treatment of the molded graphene oxide film material, combined with low-temperature reduction technology, a high-efficiency separation and high ion selective graphene oxide film was prepared. Steam treatment uses plasticized steam, such as ethanol or isopropanol, to achieve coplanar tensile orientation of the film through compressive stress of solvent steam, and to remove wrinkles and irregular morphology of the sheet layer through isotropic stretching, thereby improving the assembly order of the sheet layer and interlayer binding force.
The separation performance and selectivity of graphene oxide film are significantly improved, the mechanical stability and chemical stability of the film are enhanced, and the high selective screening of specific substances is achieved, which improves the performance of ion separation applications.
Smart Images

Figure CN119633613A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation, and relates to a highly efficient separation and high ion selectivity graphene oxide membrane and a preparation method and application thereof. Background Art
[0002] Membrane separation technology is considered one of the most important scientific methods to solve the global water crisis, and the performance of membrane materials is one of the key factors in the development of membrane separation technology. In recent years, nanomaterials, such as nano-silicon dioxide, nano-titanium dioxide, nano-silver, and carbon nanotubes (CNTs), have been widely used to develop high-performance membrane materials. In addition, two-dimensional (2D) materials have been studied to achieve advanced separation performance due to their atomic thickness, porous or non-porous structure, solution processability, chemical stability, and thermal stability.
[0003] Two-dimensional materials such as graphene-based materials, transition metal disulfides, covalent organic frameworks, metal-organic frameworks (MOFs), MXenes, layered double hydroxides (LDHs) and layered silicates have shown great potential in ion transport applications, especially ion separation and storage, due to their excellent properties. In particular, 2D nanosheets are ideal materials for building ultra-thin films due to their atomic-level thickness and micron-level lateral size. The 2D channels formed by the stacking of these nanosheets can achieve rapid and selective transport of ions or molecules.
[0004] Through research, researchers discovered the sieving properties of graphene oxide membranes (GO membranes), which can effectively block solutes with a radius greater than 0.45 nm while allowing ions with a smaller hydration radius to pass through. Subsequent studies further confirmed the key role of interlayer channels in the selective transport of ions and molecules. At the same time, it was proved that an ideal separation membrane should have the advantages of short channels with high permeability, precisely controllable selective channel size, and high chemical and mechanical stability. Therefore, the rational regulation of interlayer channels is crucial.
[0005] Graphene-based materials are the most studied nanoporous membranes, multilayer membranes, and mixed matrix membranes. Molecular dynamics simulation results show that the water permeability of nanoporous graphene is several orders of magnitude higher than that of conventional reverse osmosis membranes. On the other hand, like most nanomaterials, graphene-based materials have been modified for use in ultrafiltration (UF), nanofiltration (NF), reverse osmosis (RO), forward osmosis (FO), conventional separation membranes for ion exchange, pervaporation, and gas separation.
[0006] GO membranes assembled from GO nanosheets have shown excellent separation performance potential, and GO nanosheets are inexpensive to mass produce and easy to study. However, GO membranes are susceptible to the hydrophilicity of GO nanosheets, which causes water molecules to easily insert into the interlayer channels, destroying the ordered structure of the membrane and reducing the separation performance. The original interlayer distance of the GO membrane is about 0.45nm, but in aqueous solution, due to the hydration of oxygen-containing groups on the GO nanosheets, the interlayer distance will expand to about 0.9nm, which makes the membrane unable to effectively block the transmission of hydrated ions. Therefore, how to prevent GO nanosheets from swelling during the separation process and maintain high separation performance is a key challenge facing GO membranes.
[0007] In the process of preparing GO membranes, due to the low Young's modulus and shear modulus of GO sheets, small bending stiffness and film elastic modulus, folding, curling and wrinkling may occur during the assembly process, as well as wrinkles caused by edge-to-edge interaction between adjacent GO sheets, which leads to low sheet assembly order, low stacking orientation, high membrane porosity, and uncontrollable pore distribution. These problems also lead to defects that hinder stress transmission in the membrane, as well as pores of varying sizes and tortuous paths, which reduce the ion transmission efficiency and ion selectivity, and then affect the mechanical and chemical stability of the graphene oxide membrane, as well as the separation efficiency and separation selectivity. Therefore, how to accurately control the interlayer nanochannels in the graphene oxide membrane and shorten the interlayer spacing, while improving the sheet assembly order and stacking orientation, is crucial to improving stability and separation performance.
[0008] In order to give full play to the theoretical advantages of GO membranes, researchers have proposed a variety of technologies aimed at developing stable, scalable and highly permeable / selective GO membranes to ensure that the interlayer nanochannels in the GO membrane can be precisely controlled, the interlayer spacing can be shortened, and the orderliness of the sheet assembly and the stacking orientation can be improved, thereby significantly improving the stability and separation performance of the GO membrane.
[0009] Reference 1 (ACS Nano, 2022, 16(6): 8869-8880) proposed a chemical structural engineering strategy to reduce the carboxyl groups on the edge of GO, which achieved the spontaneous ordered stacking of GO (GO-m) with trace carboxyl groups and improved the packing density. This is because the fewer carboxyl groups on the edge weaken the interlayer hydrogen bonding effect, and the interfacial friction between the sheets at the atomic scale is reduced, which helps to increase the packing density. The GO film obtained from low-carboxyl GO has a higher degree of orientation, with a Herman's orientation factor of 0.94 (greater than 0.87 of the high-carboxyl content film), a half-peak width (FWHM) of 7°, a higher degree of orientation, a tensile strength of 631 MPa, and a fracture energy of 3.47 MJ·m -3However, there are still limitations in further improving the stacking density of the sheets and eliminating the pores between the stacks, making it difficult to improve the orderliness and orientation of the stacking structure to a higher level.
[0010] Reference 2 (Nano Letter 2017, 17, 2928−2933) controls the deposition rate to adjust the self-assembly arrangement of GO, so that the π-π domains on the sheets are opposite to each other and the oxidized regions are opposite to each other, thus achieving a good interlayer nanostructure, increasing the desalination rate by 1.8 to 4 times, the water permeability by 2.5 to 4 times, and better size-dependent sieving performance (Na + The interception rate was increased by 2 times). However, this method cannot increase the stacking density between the sheets to a greater extent, and cannot control the stacking orientation.
[0011] Reference 3 (Nano Lett. 2023, 23, 9641-9650) mentioned that the wrinkles on the GO sheet were flattened by vortex shearing, so that it was tightly packed into an ultra-flat GO membrane with a Newton ring interference pattern. As the mechanical stirring speed increases, the interlayer spacing of the GO membrane decreases, the stability of the interlayer structure increases, and the water flux increases by 3 times, which has an impact on K + / Mg 2+ The separation factor of ions is about 57.92, which is equivalent to Li + / Mg 2+ and K + / Mg 2+ The results showed good separation effect, with separation factors reaching about 68.02 and 379.17 at 9 h, respectively. However, the vortex shear flattening process makes it difficult to accurately control the stacking of different thicknesses, resulting in inconsistent interlayer spacing and orientation distribution in the GO membrane, affecting the overall separation performance of the membrane. In addition, this method cannot prepare highly oriented membranes on a large area.
[0012] Patent CN118239483A discloses a method for preparing a self-supporting graphite film and a soft X-ray detector. The method mentions that the solvent is used to form a circumferential shear during the centrifugal escape process to orient the sheets to prepare a composite film with controllable size, orientation, and humidity, and then the controllable phase separation technology is used to achieve rapid separation of the GO film and the substrate. The film prepared by this method has a high degree of orientation, which can reach 98.6%. However, this method takes a long time to prepare the film, and has high costs and energy consumption, so it cannot be promoted on a large scale.
[0013] Reference 4 (Nano-Micro Lett. 2024, 16:17) mentions that in-plane mechanical stretching is performed during the drying process to suppress the inward contraction caused by the capillary force generated by solvent evaporation, so as to eliminate the wrinkles of graphene oxide nanosheets and achieve high in-plane orientation of graphene oxide nanosheets. After reduction, a graphene film is obtained for high thermal conductivity applications. However, when the external force is unloaded, the induced oriented structure may partially rebound and fail to maintain a stable in-film structure.
[0014] Reference 5 (Environmental Science & Technology Letters, 2020, 7(4): 273-279) mentioned that three different reduction methods were used to study the effect of GO membrane wrinkle density. Compared with rGO membranes reduced by thermal annealing in vacuum and HI (hydriodic acid) vapor, rGO membranes prepared by thermal reduction in air showed the highest water permeability and NaCl rejection rate. This is because the wrinkle density in the rGO membrane reduced in air is the lowest, which inhibits the permeation of non-selective ions and improves the separation selectivity. The water permeability is 1.05 LMH / bar and the NaCl removal rate reaches 83%. However, the increase in pores in the membrane and the decrease in the order of the sheets during the reduction process cannot meet the requirements of finer screening.
[0015] Therefore, it is of great significance to have a highly efficient separation and high ion selectivity graphene oxide membrane and a preparation method and application to solve the above problems. Summary of the invention
[0016] The purpose of the present invention is to solve the problems existing in the prior art and to provide a graphene oxide membrane with high separation efficiency and high ion selectivity and a preparation method and application thereof.
[0017] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0018] A method for preparing a graphene oxide membrane with high efficiency separation and high ion selectivity, wherein the formed graphene oxide membrane material is isotropically stretched and steam treated at the same time, and then placed in a vacuum environment at 80-150°C for low-temperature reduction to obtain a partially reduced graphene oxide membrane, i.e., a graphene oxide membrane with high efficiency separation and high ion selectivity;
[0019] The steam used in the steam treatment is plasticizing steam, which is formed by evaporating a plasticizing solvent having a plasticizing effect on the graphene oxide film material, and the plasticizing solvent is ethanol or isopropanol;
[0020] When the thickness of the graphene oxide membrane material is ≤ 10 μm, the device for simultaneously performing isotropic stretching and steam treatment on the graphene oxide membrane material includes a solvent pool a and a heating device a; the top of the solvent pool a is a vertically arranged cylinder a, which is divided into upper and lower layers and is detachably connected by 2m membrane fixing screws a, where m > 2, and the 2m membrane fixing screws a are circumferentially and evenly distributed around the central axis of the cylinder a; the heating device a is used to heat the solvent pool a; the solvent vapor stress in the closed environment is converted into an isotropic tensile stress after contacting the graphene oxide membrane material fixed above, so as to simultaneously perform isotropic stretching and steam treatment on the graphene oxide membrane material; the amount of the plasticizing solvent is 30 - 100 mL, the heat preservation temperature after the plasticizing solvent vaporizes is 90 - 105 °C, the generated vapor pressure stress is 1200 - 20000 mmHg, and the heat preservation time after the plasticizing solvent vaporizes is 12 - 24 h. When using this device, since the thickness of the graphene oxide membrane material is relatively thin, the steam can penetrate into the membrane, ensuring uniform heating as the reaction time prolongs. The vapor pressure generated by the rapid diffusion of solvent molecules assists in stress control at the membrane edge, and tensile stress can be generated along the perimeter of the membrane. Therefore, coplanar tensile orientation under the assistance of vapor pressure is achieved;
[0021] When the thickness of the graphene oxide membrane material is > 10 μm, the device for simultaneously performing isotropic stretching and steam treatment on the graphene oxide membrane material includes a solvent pool b, a heating device b, a deformable tube, and a regulator; the bottom of the deformable tube is hermetically connected to the top of the solvent pool b, the top of the deformable tube is a vertically arranged cylinder b, which is divided into upper and lower layers and is detachably connected by 2m membrane fixing screws b, where m > 2, and the 2m membrane fixing screws b are circumferentially and evenly distributed around the central axis of the cylinder b; the regulator is used to control the radial outward expansion of the cylinder b; the heating device b is used to heat the solvent pool b; by controlling the outward extension of the deformable tube through the regulator, during the extension of the deformable tube, it generates an epitaxial biaxial tensile displacement of 1.5 mm - 3 mm on the circumferential boundary of the graphene oxide membrane material in contact with it, so as to simultaneously perform isotropic stretching and steam treatment on the graphene oxide membrane material. Since the thickness of the graphene oxide membrane material is too large, the steam penetration effect will be weakened, making it impossible to complete the plasticizing and stretching orientation inside the membrane and in the upper layer. Therefore, an additional in-plane isotropic stretch needs to be applied to the graphene oxide membrane material to ensure that the graphene oxide membrane material completes the plasticizing orientation process in a uniform mixed steam environment and under isotropic stretching;
[0022] Adjust the volume of the plasticizing solvent according to the area and thickness of the graphene oxide membrane material, which can be simplified to adjust the volume of the plasticizing solvent according to the mass area density (D): when 0 < D ≤ 5, 30 mL; when 5 < D ≤ 10, 50 mL; when D > 10, 100 mL; the unit of D is mg·cm -2 。
[0023] When the film thickness is ≤10 μm, the hydrogen bond network between GO sheets is dominant, and the in-plane fracture toughness is low (~1 MPa·m¹ / ²), but the isotropic tensile stress generated by steam is sufficient to induce uniform deformation dominated by elasticity; when the film thickness is greater than 10μm, the stress inhomogeneity of pure steam loading (the ratio of stress inside the film to that on the film surface) is large, and epitaxial mechanical stretching is required to provide compensatory stress gradients. That is, due to the excessive thickness, the diffusion path of plasticized steam in the film increases, and the penetration effect is greatly weakened, making it impossible to complete the tensile orientation of the inner and outer layers of the film. Therefore, it is necessary to apply additional in-plane isotropic stretching to the graphene oxide film material to ensure that the graphene oxide film material completes the reduction orientation process under a uniform mixed steam environment and isotropic stretching.
[0024] When the thickness of the graphene oxide film material is ≤10μm, the graphene oxide film is fixed circumferentially by the vertically arranged cylinder a and the film fixing screw a to form a closed cylindrical reaction chamber, forming an axisymmetric constraint boundary condition system. The saturated vapor pressure of the plasticizing solvent in the system is controlled by the constant temperature field. When the volume and temperature of the solvent reach the conditions for generating saturated vapor pressure, its vapor molecules penetrate into the graphene oxide interlayer domain through Knudsen diffusion. The plasticizing vapor penetration reduces the interlayer slip barrier, causing the film to enter a high plastic state, producing a steam plasticizing effect; at the same time, the internal and external vapor pressure difference produces a uniform normal stress distribution in the film plane. Constrained by the axisymmetric boundary, the graphene oxide film undergoes a planar equibiaxial tensile deformation, and its strain tensor satisfies the isotropic condition, thus achieving simultaneous isotropic stretching and steam treatment of the graphene oxide film material.
[0025] When the thickness of the graphene oxide film material is >10μm, a circumferential displacement loading component (deformable tube and regulator) is integrated on the basis of the original closed steam chamber. When the regulator controls the outward extension of the deformable tube, during the extension of the deformable tube, it produces an epitaxial equibiaxial tensile displacement (△L) on the circumferential boundary of the membrane in contact with it, thereby generating external tensile stress. The external tensile stress forms a uniform strain field in the plane, thereby realizing the simultaneous isotropic stretching and steam treatment of the graphene oxide film material.
[0026] When the present invention simultaneously performs isotropic stretching and steam treatment on the formed graphene oxide membrane material, the plasticized steam molecules can penetrate the graphene oxide layers to weaken the interlayer van der Waals force and improve the deformation capacity of the sheets. The isotropic stretching can remove or reduce the wrinkles, wrinkles and other irregular shapes of the sheets, so that they can be aligned and assembled more evenly, improve the assembly order of the sheets (tighter and more orderly interlayer assembly), increase the interlayer bonding force (reduce the interlayer spacing), and improve the orientation of the sheet stacking domain (increase the stacking domain density and reduce the internal pores). The improvement of the interlayer assembly order, the reduction of the interlayer spacing and the increase of the orientation of the sheet stacking domain make the permeation path of water and ions in the membrane shorter, accelerate the permeation rate, significantly improve the transmission efficiency, and improve the water permeation flux and interception rate; in addition, the finely adjustable interlayer spacing can achieve high selectivity for screening specific substances, so that the high-efficiency separation and high ion selectivity graphene oxide membrane show more superior performance in ion separation applications.
[0027] The specific mechanism of action of plasticizing steam is as follows: Figure 1 As shown in (a), when the untreated graphene oxide is dialyzed to separate monovalent / divalent ions in aqueous solution, the monovalent and divalent ions cannot be completely separated due to the disordered stacking of the interlayer sheets in the membrane and the large number of irregular gaps. In addition, the water permeation path is tortuous and the permeation rate is slow. Figure 1 As shown in (b), when the graphene oxide film is subjected to plasticizing solvent vapor-assisted coplanar stretching, the plasticizing vapor molecules can penetrate into the graphene oxide layers by diffusion. When ethanol or isopropanol is used as the plasticizing solvent, the solvent molecules generate hydrogen bonds, van der Waals forces and wetting effects with the oxygen-containing functional groups on the graphene oxide, and can penetrate into the graphene oxide layers and interact with the layers by hydrogen bonds and van der Waals forces, thereby reducing the interlayer cohesion and interlayer slip resistance, thereby improving the deformability and slip ability of the layers. At the same time, the solvent molecules replace the positions occupied by some of the bound water molecules in the layers, reducing the amount of bound water between the layers. The plasticizing vapor can increase the molecular mobility on the surface of the layers, and some molecular segments are "softened" by the plasticizing vapor molecules in the vapor. This softening effect increases the translational entropy, rotational entropy and kinetic entropy of the layers, making it easier for the layers to reach an ordered stacking state after being flattened and stretched. At the same time, due to the wetting effect of the plasticizing vapor molecules, the internal stress is partially released, as shown in FIG. Figure 1As shown in (c), under the action of isotropic stretching, the lamellae stretch more evenly, eliminating wrinkles within the lamellae and irregular stacking between lamellae, thereby forming a more compact and ordered assembly structure; further, under the action of continuous isotropic stretching, the lamellae are guided to be flatter in all directions within the plane, and the lamellae are arranged more evenly, avoiding the anisotropy formed by directional rearrangement, reducing the disorder of the overall stacking, promoting uniform stacking arrangement, and increasing stacking orientation; in addition, after the plasticization is completed, with the slow evaporation of the plasticizing vapor, the lamellae tend to rearrange into a tighter structure, which will increase the stacking height and gradually reduce the interlayer spacing accordingly. This change leads to a gradual increase in the bonding force between the lamellae and an increase in the failure stress of interface slip. Furthermore, the ordered arrangement and orientation of the stacking domains of the lamellae are enhanced with the rearrangement, which gradually reduces the disordered pores in the membrane and increases the interface failure stress between domains, thereby increasing the overall tensile strength of the membrane, as shown in FIG. Figure 1 As shown in (d), when the treated graphene oxide membrane is dialyzed to separate monovalent / divalent ion aqueous solution, small-sized monovalent ions can be separated more fully, and the monovalent / divalent ion separation selectivity is greatly increased. The permeation path of water molecules in the sheet is also shorter and more efficient, and the water permeability is correspondingly improved. Based on the above analysis, the overall interlayer spacing in the membrane is precisely controllable, the interlayer bonding force is increased, and the disordered defects are reduced, which enhances the mechanical and chemical stability of the membrane.
[0028] Isotropic stretching is more conducive to improving the performance of graphene oxide film materials than uniaxial and biaxial stretching in the prior art, because the tensile stress on the periphery of the film is evenly distributed in all directions during isotropic stretching. Compared with uniaxial and biaxial stretching, the stress distribution inside the film and the influence of the orientation of the lamellae will be significantly different: (1) Isotropic stretching: When isotropic stretching is performed on the film, the stress will be evenly distributed from the center to the outside, and the lamellae will not be stretched biasedly in a specific direction. Uniform stretching will cause the lamellae inside the film to be subjected to the same tensile force in all directions at the same time, flattening and stretching along all directions of the plane, releasing wrinkles and folds caused by uneven stress. Multi-directional stress helps to flatten the lamellae and reduce uneven wrinkles. Isotropic stretching helps to form an orderly stacking without deviation in a specific direction, which can make it easier for the lamellae to reach a stable ordered state and reduce complex mutual entanglement. Under isotropic stretching, the lamellae are guided to be arranged more evenly in all directions within the plane, avoiding the anisotropy formed by directional rearrangement, reducing the disorder of the overall stacking domain, and promoting uniform arrangement of the stacking domain. Therefore, the lamellae orientation will be evenly distributed in the plane direction, and there will be no inconsistent distribution of the stacking domain due to obvious single orientation, avoiding stress concentration in any local direction. (2) Uniaxial stretching: Stress is applied in a single direction, so that the stress is concentrated in the stretching direction. The lamellae in the film are flat along the uniaxial direction and rearranged roughly parallel to the stretching direction, while shrinkage occurs in the perpendicular direction of the uniaxial direction (Poisson effect), resulting in an increase in the order and orientation of the lamellae along the stretching direction, but it is obviously insufficient in the direction perpendicular to the stretching direction; (3) Biaxial stretching: Stress is applied in the orthogonal direction, and the stress needs to be controlled to be consistent in the two directions. The lamellae in the film tend to be flat and rearranged along the biaxial directions, which to a certain extent enhances the orderly stacking and orientation of the lamellae, especially in the two main axis directions. However, the wrinkle release and orderly arrangement on the non-main stress axis are not as good as isotropic stretching, which easily leads to the problem of excessive stress concentration load in the local direction.
[0029] After the graphene oxide membrane is plasticized by steam and isotropically stretched, the orderliness and controllability of the structure in the membrane increase. During the separation of the aqueous phase, the graphene oxide membrane will inevitably be swollen by water molecules. The swelling comes from the hydrogen bond interaction between the oxygen-containing functional groups on the graphene oxide and water molecules or other polar solvents. In the swollen state, the interlayer spacing of the graphene oxide membrane increases (15~60 Å, depending on the pH value, ionic strength or external pressure of the solution), which significantly reduces the separation ability and selectivity of the membrane and even causes the dissociation of the membrane. Therefore, in order to maintain the efficient separation and high selectivity of the graphene oxide membrane, the graphene oxide membrane is reduced at low temperature to partially remove the oxygen-containing functional groups (hydroxyl and epoxy groups) on the sheet to reduce its interaction with water molecules or other polar solvents, thereby inhibiting swelling. After partial reduction, the π-π structure on the graphene layer increases, the interlayer π-π interaction is enhanced, and the overall stability of the membrane is improved. At the same time, the partially reduced GO exhibits higher hydrophobicity, increases the permeation rate of water between the layers, and stabilizes the separation selectivity of the membrane.
[0030] As the preferred technical solution:
[0031] In the method for preparing the graphene oxide membrane with high separation efficiency and high ion selectivity as described above, the thickness of the graphene oxide membrane material is 10nm~50μm.
[0032] The method for preparing the graphene oxide membrane with high efficiency separation and high ion selectivity as described above, wherein the regulator comprises a displacement bracket, a pressing plate, an upper bracket, a limiting structure and a lower bracket;
[0033] The displacement bracket is a conical cap-shaped structure with the tip at the top, comprising 2n inclined rods I, n>3, the upper ends of the 2n inclined rods I are simultaneously connected to the center of the lower surface of the pressing plate, and the lower ends are evenly distributed around a point o, the point o is located on the central axis of the pressing plate, and the pressing plate is coaxial with the cylinder b;
[0034] The upper support includes 2n horizontal rods, which are radially distributed around point o. The two ends of the horizontal rods are respectively marked as end a and end b. End a is closer to point o than end b. The ends a of the 2n horizontal rods are respectively hinged to the lower ends of the 2n oblique rods I in a one-to-one correspondence.
[0035] The limiting structure restricts the 2n horizontal rods to move only along their own length direction;
[0036] The b ends of two adjacent horizontal rods are each connected by an arc bar, and at least one set of opposite arc bars is composed of three sections: left, middle and right. The middle section is composed of a separated inner layer and outer layer. The outer layer of the middle section is fixedly connected to the left section, and the inner layer of the middle section is fixedly connected to the right section. All the arc bars form a circular ring, and the circular ring extends vertically downward to form a circular tube.
[0037] The lower support includes 2n oblique rods II, which are distributed in an umbrella shape around the central axis of the cylinder b. The angle between the oblique rods II and the central axis of the cylinder b is 100-105°. The lower layer of the cylinder b extends radially outward and is connected to the upper ends of the 2n oblique rods II, and the lower ends of the 2n oblique rods II are connected to the circular tube.
[0038] When the pressing plate is subjected to downward pressure, it will move downward. This displacement is transmitted to the upper bracket through the displacement bracket, causing the upper bracket to move outward. Then, the displacement of the upper bracket is transmitted to the lower bracket, causing the lower bracket to move outward as well. Finally, the displacement of the lower bracket is transmitted to the deformable tube, causing the deformable tube to extend outward. In the process of the deformable tube extending outward, it applies a coplanar tensile displacement to the edge of the membrane in contact with it, thereby generating tensile stress.
[0039] For graphene oxide film materials with a thickness greater than 10 μm, due to the large thickness, the steam penetration effect is weakened, and the plasticization stretching orientation inside and on the upper layer of the graphene oxide film material cannot be completed. It is necessary to start the stretching device to apply additional in-plane isotropic stretching to the graphene oxide film material to ensure that the graphene oxide film material completes the plasticization stretching orientation process under a uniformly mixed steam environment and isotropic stretching. Among them, the maximum stretching displacement (△L) is determined by the initial diameter L0 of the graphene oxide film material, and the shrinkage rate of the unstretched film on the plane before and after plasticization stretching orientation is , maximum tensile displacement △L= (L0* ) / 2.
[0040] Shrinkage rate of graphene oxide film material on the plane (%) can be calculated experimentally (i.e., the graphene oxide film material is placed in a vacuum environment at 100°C for 12 hours, during which time the vacuum is continuously drawn, and then the average diameter L is measured after it is taken out and cooled to room temperature. T ), the shrinkage rate is calculated as follows:
[0041] ;
[0042] The tensile displacement is controlled by the pressing plate above the device. Below the pressing plate is the length S of the inclined rod I that can control the outward movement of the edge (the initial angle between the inclined rod I and the pressing plate is 45°), which is used to control the outward movement of the upper and lower brackets. When the downward pressing distance is controlled (the height measuring bracket can record the change), the outward movement of the lower bracket causes the deformable tube to extend outward, thereby generating an outward coplanar tensile displacement of the graphene oxide film material fixed on the deformable tube. Since the maximum tensile displacement is related to the maximum pressing displacement, the calculation formula for the maximum pressing displacement △H is as follows:
[0043] ;
[0044] In the formula, S is the length of the inclined rod I of the displacement bracket, and H is the initial height of the displacement bracket (i.e., the vertical distance between the pressing disc and the upper bracket);
[0045] Substitute the planar shrinkage rate and the calculation formula of the initial diameter L0 of the graphene oxide membrane material, and the final calculation formula is:
[0046] ;
[0047] Therefore, after determining the length S of the displacement bracket and the initial height H of the displacement bracket, the maximum pressing displacement can be adjusted according to the initial diameter L0 of the graphene oxide membrane material and the diameter L of the graphene oxide membrane material after shrinkage T to adjust the actual pressing displacement not exceeding the maximum pressing displacement, which is adjusted according to the required stretching ratio. The stretching ratio is y (0 < y < 1), and the actual pressing displacement is y * △H. Adjust the actual pressing displacement according to the application requirements.
[0048] In the present invention, the designed lower bracket includes 2n inclined rods II. On the one hand, it is to disperse the extended external force to the entire plane, reduce the stress concentration in a single direction, and avoid stress overload in a local direction; on the other hand, it is to provide a small displacement to cause a small deformation of the deformable tube.
[0049] For the preparation method of the high-efficiency separation and high-ion-selectivity graphene oxide membrane as described above, the regulator further includes a height-measuring bracket, which is vertically arranged on one side of the pressing disc and fixedly connected to the upper bracket.
[0050] For the preparation method of the high-efficiency separation and high-ion-selectivity graphene oxide membrane as described above, the forming method of the graphene oxide membrane material is: vacuum filtering the graphene oxide aqueous solution into a film, spin-coating multiple times into a film, casting on a substrate and evaporating and assembling into a film, or continuously scraping and coating into a film, and then drying and forming to obtain the graphene oxide membrane material; among them, when using vacuum filtration to form a film, the concentration of the graphene oxide aqueous solution used is 0.5 - 1.5 mg·g -1 , when using spin-coating multiple times to form a film, the concentration of the graphene oxide aqueous solution used is 1 - 5 mg·g -1 , when using casting on a substrate and evaporating and assembling into a film, the concentration of the graphene oxide aqueous solution used is 6 - 8 mg·g -1 , when using continuous scraping and coating to form a film, the concentration of the graphene oxide aqueous solution used is 20 - 40 mg·g -1 .
[0051] According to the method for preparing the graphene oxide membrane with high efficiency separation and high ion selectivity as described above, the interlayer spacing of the graphene oxide membrane material is 0.35~0.8nm, the tensile strength is 20~300MPa, the sheet stacking domain height is 3~9nm, and the Herman's orientation factor is 0.2~0.5; after the graphene oxide membrane material swells in water, the interlayer spacing increases to 0.45~1nm.
[0052] The present invention also provides a high-efficiency separation and high ion selectivity graphene oxide membrane prepared by the preparation method as described in any one of the above items, the tensile strength of the high-efficiency separation and high ion selectivity graphene oxide membrane is 50-750MPa, indicating that the mechanical stability is improved, the interlayer spacing is 0.3-0.4nm, the sheet stacking domain height is 5-12nm, and the Herman's orientation factor is 0.3-0.95; after the high-efficiency separation and high ion selectivity graphene oxide membrane swells in water, the interlayer spacing increases to 0.32-0.45nm. The "stacking domain height of the membrane" characterizes the orderliness of the lamellar stacking; the "Herman's orientation parameter S of the membrane" characterizes the spatial arrangement and orientation distribution of the two-dimensional lamellar layers, and quantifies whether the two-dimensional lamellar stacking domain has a consistent arrangement direction, that is, the orientation degree of the internal structure. The orientation factor ranges from 0 to 1. When the orientation factor is 0, the lamellar stacking domains are distributed in a completely random manner. When the orientation factor is 0.5, the lamellar stacking domains show a partially ordered arrangement, but there are still randomly distributed stacking domains. When the orientation factor is 1, the lamellar stacking domains are arranged along a consistent direction.
[0053] The present invention also provides the use of the graphene oxide membrane with high separation efficiency and high ion selectivity as described above, which is used as an ion separation membrane;
[0054] Using graphene oxide membrane material as the ion separation membrane, the water permeability is 10~93LMH / bar, the inorganic salt retention rate is 10~50%, the dye retention rate is 70~90%, and the divalent / monovalent ion screening selectivity factor is 1~3; after 120 hours of continuous testing, the water permeability of the graphene oxide membrane material decreased by 50~80%;
[0055] The water permeability of the graphene oxide membrane with high efficiency separation and high ion selectivity is 30~600LMH / bar, LMH stands for liters per square meter per hour (L / m²·h), and bar is the unit of pressure. LMH / bar is used to describe the water permeability of the selective graphene oxide membrane under unit pressure difference. A higher LMH / bar indicates a larger water flux under a lower pressure difference, indicating a more efficient separation ability and lower energy consumption. The inorganic salt retention rate is 70~95%, the dye retention rate is 85~99%, and the divalent / monovalent ion screening selectivity factor is 10~50. After 120 hours of continuous testing, the water permeability of the graphene oxide membrane with high efficiency separation and high ion selectivity decreased by 10-20%, indicating that the chemical stability has been significantly improved.
[0056] Beneficial effects:
[0057] (1) The steam-assisted isotropic stretching orientation method used in the present invention can simultaneously improve the stacking order and stacking orientation of the lamellae in the membrane, thereby enhancing the mechanical stability and chemical stability of the membrane, and precisely control the interlayer nanochannels to improve the permeation efficiency and separation selectivity.
[0058] (2) The finely adjustable interlayer spacing of the present invention can achieve high selectivity for screening specific substances, thereby enabling the high-efficiency separation and high-ion selectivity graphene oxide membrane to exhibit superior performance in ion separation applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 The present invention is a schematic diagram of the changes in the structure of the graphene oxide membrane before and after steam plasticization and stretching, as well as the changes in water transmission and ion screening selectivity; in the figure, a represents the disordered stacking of irregular GO sheets in the graphene oxide membrane, and the water transmission channel is tortuous, and specific ions cannot be screened; b represents that the solvent molecules penetrate the interlayers of the graphene oxide membrane to weaken the interlayer Van der Waals force and improve the sheet slip ability; c represents that the sheets in the graphene oxide membrane tend to be flat and assembled, the interlayer spacing is reduced, and the sheet assembly order and stacking orientation are increased; d represents that the transmission path in the graphene oxide membrane is shortened, the water permeation flux is increased, the solute retention rate is increased, and the ion selectivity is increased;
[0060] Figure 2 is a schematic diagram of an isotropic stretching and steam treatment device in Example A1 of the present invention;
[0061] Figure 3 is a top view of the isotropic stretching and steam treatment device in Example A1 of the present invention;
[0062] Figure 4Schematic diagram of the isotropic stretching and steam treatment device in Example A2 of the present invention; in the figure, 45° is the initial angle; S is the length of the inclined rod I of the displacement bracket; H is the initial height of the displacement bracket, that is, the vertical distance between the pressing plate and the upper bracket; △H is the maximum pressing displacement; △L is the maximum stretching displacement;
[0063] Figure 5 is a top view of the regulator in Example A2 of the present invention;
[0064] Figure 6 It is a side view of the middle section of the arc strip in the upper support of the present invention;
[0065] Among them, 1-solvent pool a, 2-cylinder a, 3-membrane fixing screw a, 4-arc bar, 5-solvent pool b, 6-height measuring bracket, 7-limiting structure, 8-membrane fixing screw b, 9-deformable tube, 10-displacement bracket, 11-pressing plate, 12-upper bracket, 13-lower bracket. DETAILED DESCRIPTION
[0066] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0067] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:
[0068] Mass area density D: Mass area density D = concentration of graphene oxide aqueous solution (mg g -1 )×mass of graphene oxide aqueous solution (g) / area of graphene oxide film material (cm 2 ), unit is mg cm -2 .
[0069] Interlayer spacing: The high-efficiency separation and high ion selectivity graphene oxide membrane and graphene oxide membrane material prepared in each embodiment were used as samples, and then the samples were subjected to X-ray diffraction (XRD) test. According to the obtained diffraction pattern, combined with the Bragg law equation (nλ=2dsinθ), the interlayer spacing d was calculated by substituting the ray wavelength λ, diffraction angle θ and diffraction order n (n is 1).
[0070] Height of sheet stacking domain: The high-efficiency separation and high-ion selectivity graphene oxide membrane and graphene oxide membrane material prepared in each embodiment are respectively used as samples, and then the samples are subjected to XRD test. According to the obtained diffraction pattern, combined with the Scherrer formula (L c=Kλ / FWHM·cosθ), substituting the Scherrer constant K (K value is 0.9), the ray wavelength λ, the ordered stacking domain diffraction peak angle θ and the half-peak width FWHM of the XRD diffraction peak (that is, the difference of the diffraction angle 2θ at half the peak value of the diffraction peak is the half-peak width of the XRD diffraction peak) to calculate the stacking domain height L c .
[0071] Tensile strength: The high-efficiency separation and high ion selectivity graphene oxide membrane and graphene oxide membrane material prepared in each embodiment were used as samples, respectively. When the thickness of the sample was ≤10 μm, a tensile compression dynamometer (model: American Mark-10 IntelliMESUR 2.3.1) was used to test the tensile strength of the sample. When the thickness of the sample was >10 μm, an electronic universal material testing machine (model: INSTRON 5969) was used to test the tensile strength of the sample.
[0072] Herman's orientation factor: The high-efficiency separation and high-ion selectivity graphene oxide membrane and graphene oxide membrane material prepared in each embodiment are used as samples, and then the samples are subjected to the small-angle X-ray scattering (SAXS) of the BL16B1 beamline of the Shanghai Light Source Synchrotron Radiation Station to obtain the scattering intensity distribution of the diffraction spot. Finally, the scattering intensity distribution is processed and the azimuth angle is calculated. As a variable, the scattering intensity I( ), the weighted average of the scattering intensity at different azimuth angles is obtained by integration ⟨cos 2 >, according to the Herman's orientation factor calculation formula, the Herman's orientation factor is obtained, and the calculation formula is: Herman's orientation factor = .
[0073] Water permeability: The graphene oxide membrane prepared in each embodiment and the high-efficiency separation and high ion-selective graphene oxide membrane used as an ion separation membrane were used as samples, respectively. The samples were then installed on a nanofiltration test device and tested using ultrapure water (conductivity less than 0.1µS / cm) at a set pressure in the range of 1 to 10 bar (adjusted according to the thickness of the sample). The amount of water passing through the sample within a certain time interval was recorded, and the water permeation flux J (L / m²·h) was calculated according to the formula, which is: , where V is the volume of the permeate, in L; A is the effective filtration area of the sample, in m 2 ; △t is the filtering time, unit is h.
[0074] Inorganic salt retention rate: The high-efficiency separation and high-ion-selective graphene oxide membranes used as ion separation membranes in each embodiment were used as samples, and the effective test area of the samples was 13.8 cm 2, first prepare solution A (the concentration of lithium chloride is 2g L -1 , the concentration of potassium chloride is 2 g L -1 , the concentration of sodium chloride is 2 g L -1 , the solvent is water), and then the sample is fixed in the middle of the nanofiltration membrane test device through anodized aluminum membranes (pore size 100nm, porosity 10%) above and below the sample. 50mL of solution A is placed in the left pool of the device as the feed solution, and 50mL of ultrapure water (driving solution) is placed in the right pool of the device. In order to reduce concentration polarization, magnetic particles are placed in the pools on both sides of the device to stir at a speed of 500rpm. A pressure of 0.5MPa is applied at 25℃ for 1h to obtain a stable flux. Subsequently, 1mL of solution is regularly extracted from the left and right sides, and inductively coupled plasma optical emission spectrometry (ICP-OES) is used. The concentration changes of lithium ions, potassium ions and sodium ions in the solutions on both sides were measured until the concentration of the solutions sampled twice in a row did not change. Then the sampling and testing were stopped. Finally, the permeate and the concentrate were collected. The ion concentrations in the permeate in the right pool and the concentrate in the left pool were measured using ICP-OES. Then, the solute retention rate (i.e., inorganic salt retention rate) was obtained according to the calculation formula. Then, the solute retention rate of the samples prepared in the same embodiment was tested according to the aforementioned method, and the average value was finally calculated (the pipeline was thoroughly cleaned with deionized water after each test to ensure the accuracy of the experimental results). Among them, the calculation formula of the inorganic salt retention rate is: , where C P is the solute mass concentration in the permeate, is the solute mass concentration in the feed solution.
[0075] Dye retention rate: The high-efficiency separation and high-ion-selective graphene oxide membranes used as ion separation membranes in each embodiment were used as samples, and the effective test area of the samples was 13.8 cm 2 , first prepare solution B (concentration 100 mg L -1The sample was fixed in the middle of the nanofiltration membrane test device through an anodic aluminum membrane (Whatman, with an average pore size of 0.02 μm) above and below the sample. 50 mL of solution B was placed in the left pool of the device as the feed solution, and 50 mL of ultrapure water (driving solution) was placed in the right pool of the device. In order to reduce concentration polarization, magnetic particles were placed in the pools on both sides of the device for uniform stirring. A pressure of 0.5 MPa was applied at 25 °C for 1 h to obtain a stable flux. 1 mL of solution was regularly extracted from the left and right sides, and an ultraviolet-visible-near infrared (UV-vis-NIR) spectrophotometer (Thermo Fisher Genesys150) was used to measure the concentration change of the dye in the solutions on both sides. When there was no change in the concentration of the solution sampled twice in a row, sampling and testing were stopped. Finally, the permeate and concentrate were collected, and the dye concentrations in the permeate in the right pool and the concentrate in the left pool were measured using ICP-OES. Then, the solute retention rate (i.e., dye retention rate) was obtained according to the calculation formula. Then, the retention rate of the solutes of the samples prepared in the same embodiment 5 was tested according to the aforementioned method, and the average value was finally calculated (the pipeline was thoroughly cleaned with deionized water after each test to ensure the accuracy of the experimental results); wherein, the calculation formula of the dye retention rate is: , where C P is the solute mass concentration in the permeate, is the solute mass concentration in the feed solution.
[0076] Divalent / monovalent ion screening selectivity factor: The high-efficiency separation and high-ion selectivity graphene oxide membranes used as ion separation membranes in each embodiment were used as samples, respectively. NaCl (Na + )、MgSO4(Mg 2+ ) and water to obtain solution C (the concentration of NaCl is 500 mg L -1 , the concentration of MgSO4 is 500 mg L -1), and then fix the sample in the middle of the nanofiltration membrane test device through an anodic aluminum membrane (pore size 100nm, porosity 10%) above and below the sample, and fill 50mL of solution C as the feed solution in the left pool of the device, and fill 50mL of ultrapure water (driving solution) in the right pool of the device. In order to reduce concentration polarization, magnetic particles are placed in the pools on both sides of the device for uniform stirring, and a pressure of 0.5MPa is applied at 25℃ for 1h to obtain a stable flux. 1mL of solution is regularly extracted from the left and right sides, and the changes in the concentrations of lithium ions, potassium ions, and sodium ions in the solutions on both sides are measured by inductively coupled plasma optical emission spectrometry (ICP-OES). When the concentration of the solution sampled twice in a row does not change, sampling and testing are stopped. Finally, the permeate and concentrate are collected, and the ion concentrations in the permeate in the right pool and the concentrate in the left pool are measured by ICP-OES. Then, the ion retention rate is calculated according to the measured results (the calculation formula is: , where C P is the solute mass concentration of a specific ion in the permeate, is the solute mass concentration of a specific ion in the feed solution), and then the divalent / monovalent ion screening selectivity factor of the sample is calculated based on the interception rate of different ions obtained. The calculation formula is: , where For divalent ions (Mg 2+ ) interception rate, For monovalent ions (Na + ) retention rate.
[0077] Example A1
[0078] The apparatus used for isotropically stretching and steam treating graphene oxide film materials with a thickness of ≤10 μm is as follows: Figure 2 , Figure 3 As shown, it includes a solvent tank a1 and a heating device a;
[0079] The top of the solvent pool a is a vertically arranged cylinder a 2, which is divided into two layers, upper and lower, and is detachably connected by 2m membrane fixing screws a 3, m>2, and the 2m membrane fixing screws a 3 are evenly distributed around the circumference of the central axis of the cylinder a 2;
[0080] The heating device a is used to heat the solvent tank a1.
[0081] Example A2
[0082] The apparatus used for isotropically stretching and steam treating graphene oxide film materials with a thickness of >10 μm is as follows: Figure 4 , Figure 5 As shown, it includes a solvent tank b 5, a heating device b, a deformable tube 9 and a regulator;
[0083] The bottom of the deformable tube 9 is sealed and connected to the top of the solvent pool b 5. The top of the deformable tube 9 is a vertically arranged cylinder b. The cylinder b is divided into two layers, upper and lower, and is detachably connected by 2m membrane fixing screws b 8, m>2, and the 2m membrane fixing screws b 8 are evenly distributed around the circumference of the central axis of the cylinder b.
[0084] The heating device b is used to heat the solvent pool b 5;
[0085] The regulator is used to control the outward expansion of the cylinder b along the radial direction of the cylinder b;
[0086] The regulator includes a displacement bracket 10, a pressing plate 11, an upper bracket 12, a limiting structure 7, a lower bracket 13 and a height measuring bracket 6;
[0087] The displacement bracket 10 is a conical cap-shaped structure with the tip at the top, comprising 2n inclined rods I, n>3, the upper ends of the 2n inclined rods I are simultaneously connected to the center of the lower surface of the pressing plate 11, and the lower ends are evenly distributed around a point o, the point o is located on the central axis of the pressing plate 11, and the pressing plate 11 is coaxial with the cylinder b;
[0088] The upper support 12 includes 2n horizontal rods, which are radially distributed around point o. The two ends of the horizontal rods are respectively marked as end a and end b. End a is closer to point o than end b. End a of the 2n horizontal rods is hinged to the lower ends of the 2n oblique rods I in a one-to-one correspondence.
[0089] The limiting structure 7 restricts the 2n horizontal rods to move only along their own length direction;
[0090] like Figure 5 , Figure 6 As shown, the ends b of two adjacent horizontal rods are connected by an arc bar 4, at least one group of relative arc bars 4 is composed of three sections: left, middle and right. The middle section is composed of a separated inner layer and outer layer. The outer layer of the middle section is fixedly connected to the left section, and the inner layer of the middle section is fixedly connected to the right section. All the arc bars 4 form a circular ring, which extends vertically downward to form a circular tube.
[0091] The lower support 13 includes 2n oblique rods II, which are distributed in an umbrella shape around the central axis of the cylinder b. The angle between the oblique rods II and the central axis of the cylinder b is 100~105°. The lower layer of the cylinder b extends radially outward and is connected to the upper ends of the 2n oblique rods II, and the lower ends of the 2n oblique rods II are connected to the circular tube.
[0092] Example B1
[0093] The preparation method of graphene oxide membrane with high separation efficiency and high ion selectivity comprises the following steps:
[0094] (1) Preparation of raw materials and equipment used;
[0095] Graphene oxide aqueous solution: the solute is graphene oxide, the flake size of graphene oxide is 0.2~0.5μm, the flake thickness is 0.8nm, and the atomic ratio of carbon and oxygen is 2:1;
[0096] The apparatus used for isotropic stretching and steam treatment was the apparatus described in Example A1, m was 3, the height of the solvent pool a was 10 cm, and the volume was 30 mL;
[0097] Plasticizing solvent: isopropyl alcohol;
[0098] Filter membrane: Celgard 3501 membrane, average pore size 0.22 μm, effective filtration diameter 4 cm, area 12.57 cm 2 ;
[0099] (2) Preparation of graphene oxide film materials;
[0100] The concentration was 0.5 mg g -1 The graphene oxide aqueous solution is vacuum filtered using a filter membrane, dried at 35° C. for 24 hours after filtration, and then the filter membrane is removed to obtain a graphene oxide film material with a thickness of 1 μm.
[0101] The water permeability of the obtained graphene oxide membrane material is 65LMH / bar, and the mass area density D is 3mg·cm -2 , the interlayer spacing is 0.45nm, the tensile strength is 210MPa, the stacking domain height is 5.8nm, and the Herman's orientation factor is 0.4; the graphene oxide film material swells after being immersed in water for 12h, and the interlayer spacing of the graphene oxide film material increases to 0.58nm after swelling;
[0102] (3) When the graphene oxide membrane material obtained in step (2) is isotropically stretched and steam-treated at the same time, 30 mL of plasticizing solvent is first added to the flux pool a, and then the graphene oxide membrane material is fixed between the upper and lower layers of cylinders a by the membrane fixing screw a and the membrane fixing screw a is adjusted to keep the two-dimensional layer macroscopic assembly membrane taut, and then heated by the heating device a until the plasticizing solvent is vaporized and then kept at 100°C for 12 hours (the vapor pressure stress during the insulation process is 17000 mmHg), and finally the plasticized graphene oxide membrane material is taken out and placed in a vacuum environment at 80°C for low-temperature reduction for 24 hours to obtain a graphene oxide membrane with high separation efficiency and high ion selectivity.
[0103] The final highly efficient separation and high ion selectivity graphene oxide membrane had a tensile strength of 500 MPa, an interlayer spacing of 0.34 nm, a sheet stacking domain height of 9.4 nm, and a Herman's orientation factor of 0.7; the highly efficient separation and high ion selectivity graphene oxide membrane swelled after being immersed in water for 12 hours, and after swelling, the interlayer spacing of the highly efficient separation and high ion selectivity graphene oxide membrane increased to 0.36 nm.
[0104] Application of high-efficiency separation and high-ion selectivity graphene oxide membrane, using the high-efficiency separation and high-ion selectivity graphene oxide membrane prepared as above as ion separation membrane.
[0105] When the high-efficiency separation and high ion-selective graphene oxide membrane is used as an ion separation membrane, it is known that the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane is 390LMH / bar, the inorganic salt retention rate is 89%, the dye retention rate is 93%, and the divalent / monovalent ion screening selectivity factor is 40; after 120 hours of continuous testing (i.e., the high-efficiency separation and high ion-selective graphene oxide membrane is used as an ion separation membrane for 120 hours continuously), the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane decreased by 13%.
[0106] Example B2
[0107] The preparation method of graphene oxide membrane with high separation efficiency and high ion selectivity comprises the following steps:
[0108] (1) Preparation of raw materials and equipment used;
[0109] Graphene oxide aqueous solution: the solute is graphene oxide, the flake size of graphene oxide is 0.5~1μm, the flake thickness is 1nm, and the atomic ratio of carbon and oxygen is 2:1;
[0110] The apparatus used for isotropic stretching and steam treatment was the apparatus described in Example A1, m was 3, the height of the solvent pool a was 8 cm, and the volume was 30 mL;
[0111] Plasticizing solvent: ethanol;
[0112] (2) Preparation of graphene oxide film materials;
[0113] A clean silicon wafer was vacuum-adsorbed on a spin coater and a 2 mg·g -1The graphene oxide aqueous solution is dropped on a glass sheet, and then the spin coater is started. The graphene oxide aqueous solution is first rotated at a speed of 1000 rpm for 30 seconds and then at a speed of 3000 rpm for 60 seconds to spin the graphene oxide aqueous solution flat into a film. After the film is formed, the silicon wafer is placed on a heating table and dried at 80°C for 1 minute. After drying, this process is repeated until a film with a thickness of 10 nm is obtained. Finally, it is placed in an oven and dried at 35°C for 24 hours to obtain a graphene oxide film material; wherein, the amount of each drop is 100 μL;
[0114] The water permeability of the obtained graphene oxide membrane material is 93LMH / bar, and the mass area density D is 0.3mg·cm -2 , the interlayer spacing is 0.4nm, the tensile strength is 250MPa, the stacking domain height is 7.5nm, and the Herman's orientation factor is 0.43; the graphene oxide film material swells after being immersed in water for 12 hours, and the interlayer spacing of the graphene oxide film material increases to 0.5nm after swelling;
[0115] (3) When the graphene oxide membrane material obtained in step (2) is isotropically stretched and steam treated at the same time, 30 mL of plasticizing solvent is first added to the flux pool a, and then the graphene oxide membrane material is fixed between the upper and lower layers of cylinders a by the membrane fixing screw a and the membrane fixing screw a is adjusted to keep the two-dimensional layer macroscopic assembly membrane taut, and then heated by the heating device a until the plasticizing solvent is vaporized and then kept at 90°C for 18 hours (the vapor pressure stress during the insulation process is 1200 mmHg), and finally the plasticized graphene oxide membrane material is taken out and placed in a vacuum environment at 120°C for low-temperature reduction for 18 hours to obtain a graphene oxide membrane with high separation efficiency and high ion selectivity.
[0116] The final highly efficient separation and high ion selectivity graphene oxide membrane had a tensile strength of 650 MPa, an interlayer spacing of 0.3 nm, a sheet stacking domain height of 10.8 nm, and a Herman's orientation factor of 0.83; the highly efficient separation and high ion selectivity graphene oxide membrane swelled after being immersed in water for 12 hours, and after swelling, the interlayer spacing of the highly efficient separation and high ion selectivity graphene oxide membrane increased to 0.33 nm.
[0117] Application of high-efficiency separation and high-ion selectivity graphene oxide membrane, using the high-efficiency separation and high-ion selectivity graphene oxide membrane prepared as above as ion separation membrane.
[0118] When the high-efficiency separation and high ion-selective graphene oxide membrane is used as an ion separation membrane, it is known that the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane is 520LMH / bar, the inorganic salt retention rate is 91%, the dye retention rate is 97%, and the divalent / monovalent ion screening selectivity factor is 45; after 120 hours of continuous testing, the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane decreased by 11%.
[0119] Example B3
[0120] The preparation method of graphene oxide membrane with high separation efficiency and high ion selectivity comprises the following steps:
[0121] (1) Preparation of raw materials and equipment used;
[0122] Graphene oxide aqueous solution: the solute is graphene oxide, the flake size of graphene oxide is 1~5μm, the flake thickness is 2nm, and the atomic ratio of carbon and oxygen is 3:1;
[0123] The apparatus used for isotropic stretching and steam treatment was the apparatus described in Example A2, with n being 5, m being 4, the height of the solvent pool b being 12 cm, the volume being 150 mL, and the angle between the inclined rod II and the central axis of the cylinder b being 100°;
[0124] Plasticizing solvent: ethanol;
[0125] (2) Preparation of graphene oxide film materials;
[0126] The concentration is 7 mg g -1 A graphene oxide aqueous solution is prepared, a quartz watch glass is used as a casting substrate, and after casting, it is dried at 45° C. for 12 h, and after removing the casting substrate, a graphene oxide film material with a thickness of 35 μm is obtained;
[0127] The water permeability of the obtained graphene oxide membrane material is 30LMH / bar, and the mass area density D is 15mg·cm -2 , the interlayer spacing is 0.6nm, the tensile strength is 120MPa, the stacking domain height is 4.2nm, and the Herman's orientation factor is 0.24; the graphene oxide film material swells after being immersed in water for 18h, and the interlayer spacing of the graphene oxide film material increases to 0.72nm after swelling;
[0128] (3) When the graphene oxide membrane material obtained in step (2) is isotropically stretched and steam treated at the same time, 100 mL of plasticizing solvent is first added to the solvent pool b, and then the graphene oxide membrane material is fixed between the upper and lower cylinders b by the membrane fixing screws b and the membrane fixing screws b are adjusted to keep the two-dimensional sheet macro-assembly membrane in a taut state, and then heated by the heating device b until the plasticizing solvent is vaporized, and at the same time, the pressing plate is pressed downward and kept warm at 95°C for 24 hours (the maximum tensile displacement △L of the two-dimensional sheet macro-assembly membrane after the insulation is completed is 2 mm), and finally the plasticized graphene oxide membrane material is taken out, and the plasticized graphene oxide membrane material is placed in a vacuum environment of 150°C for low-temperature reduction for 12 hours to obtain a high-efficiency separation and high ion selectivity graphene oxide membrane.
[0129] The final highly efficient separation and high ion selectivity graphene oxide membrane had a tensile strength of 150 MPa, an interlayer spacing of 0.38 nm, a sheet stacking domain height of 6.2 nm, and a Herman's orientation factor of 0.45; the highly efficient separation and high ion selectivity graphene oxide membrane swelled after being immersed in water for 18 hours, and after swelling, the interlayer spacing of the highly efficient separation and high ion selectivity graphene oxide membrane increased to 0.4 nm.
[0130] Application of high-efficiency separation and high-ion selectivity graphene oxide membrane, using the high-efficiency separation and high-ion selectivity graphene oxide membrane prepared as above as ion separation membrane.
[0131] When the high-efficiency separation and high ion-selective graphene oxide membrane is used as an ion separation membrane, it is known that the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane is 196LMH / bar, the inorganic salt retention rate is 75%, the dye retention rate is 88%, and the divalent / monovalent ion screening selectivity factor is 25; after 120 hours of continuous testing, the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane decreased by 17%.
[0132] Example B4
[0133] The preparation method of graphene oxide membrane with high separation efficiency and high ion selectivity comprises the following steps:
[0134] (1) Preparation of raw materials and equipment used;
[0135] Graphene oxide aqueous solution: the solute is graphene oxide, the flake size of graphene oxide is 5-10 μm, the flake thickness is 5 nm, and the atomic ratio of carbon to oxygen is 3:1;
[0136] The apparatus used for isotropic stretching and steam treatment was the apparatus described in Example A2, wherein n was 4, m was 3, the height of the solvent pool b was 10 cm, the volume was 150 mL, and the angle between the inclined rod II and the central axis of the cylinder b was 105°;
[0137] Plasticizing solvent: isopropyl alcohol;
[0138] (2) Preparation of graphene oxide film materials;
[0139] The concentration is 40 mg g -1 A graphene oxide aqueous solution is prepared by a scraping process with glass as the substrate, and the scraping is followed by drying at 35° C. for 24 hours, and a graphene oxide film material with a thickness of 50 μm is obtained after removing the glass substrate;
[0140] The water permeability of the obtained graphene oxide membrane material is 10LMH / bar, and the mass area density D is 20mg·cm -2 , the interlayer spacing is 0.8nm, the tensile strength is 20MPa, the stacking domain height is 3nm, and the Herman's orientation factor is 0.2; the graphene oxide film material swells after being immersed in water for 24h, and the interlayer spacing of the graphene oxide film material increases to 1nm after swelling;
[0141] (3) When the graphene oxide membrane material obtained in step (2) is isotropically stretched and steam treated at the same time, 100 mL of plasticizing solvent is first added to the solvent pool b, and then the graphene oxide membrane material is fixed between the upper and lower cylinders b by the membrane fixing screws b and the membrane fixing screws b are adjusted to keep the two-dimensional sheet macro-assembly membrane in a taut state, and then heated by the heating device b until the plasticizing solvent is vaporized, and at the same time, the pressing plate is pressed downward and kept warm at 105°C for 24 hours (the stretching displacement of the two-dimensional sheet macro-assembly membrane after the insulation is completed is 3 mm), and finally the plasticized graphene oxide membrane material is taken out and placed in a vacuum environment at 80°C for low-temperature reduction for 24 hours to obtain a high-efficiency separation and high ion selectivity graphene oxide membrane.
[0142] The final highly efficient separation and high ion selectivity graphene oxide membrane had a tensile strength of 50 MPa, an interlayer spacing of 0.4 nm, a sheet stacking domain height of 5 nm, and a Herman's orientation factor of 0.3; the highly efficient separation and high ion selectivity graphene oxide membrane swelled after being immersed in water for 24 hours, and after swelling, the interlayer spacing of the highly efficient separation and high ion selectivity graphene oxide membrane increased to 0.45 nm.
[0143] Application of high-efficiency separation and high-ion selectivity graphene oxide membrane, using the high-efficiency separation and high-ion selectivity graphene oxide membrane prepared as above as ion separation membrane.
[0144] When the high-efficiency separation and high ion-selective graphene oxide membrane is used as an ion separation membrane, it is known that the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane is 30LMH / bar, the inorganic salt retention rate is 70%, the dye retention rate is 85%, and the divalent / monovalent ion screening selectivity factor is 10; after 120 hours of continuous testing, the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane decreased by 20%.
[0145] Example B5
[0146] The preparation method of graphene oxide membrane with high separation efficiency and high ion selectivity comprises the following steps:
[0147] (1) Preparation of raw materials and equipment used;
[0148] Graphene oxide aqueous solution: the solute is graphene oxide, the flake size of graphene oxide is 10-15 μm, the flake thickness is 8 nm, and the atomic ratio of carbon to oxygen is 4:1;
[0149] The apparatus used for isotropic stretching and steam treatment was the apparatus described in Example A1, m was 4, the height of the solvent pool a was 10 cm, and the volume was 100 mL;
[0150] Plasticizing solvent: isopropyl alcohol;
[0151] Filter membrane: Celgard 3501 membrane, average pore size 0.22 μm, effective filtration diameter 4 cm, area 12.57 cm 2 ;
[0152] (2) Preparation of graphene oxide film materials;
[0153] The concentration was 1.5 mg g -1 The graphene oxide aqueous solution is vacuum filtered using a filter membrane, and then dried at 40° C. for 18 hours. After removing the filter membrane, a graphene oxide film material with a thickness of 10 nm is obtained.
[0154] The water permeability of the obtained graphene oxide membrane material is 85LMH / bar, and the mass area density D is 0.3mg·cm -2 , the interlayer spacing is 0.35nm, the tensile strength is 300MPa, the stacking domain height is 9nm, and the Herman's orientation factor is 0.5; the graphene oxide film material swells after being immersed in water for 12h, and the interlayer spacing of the graphene oxide film material increases to 0.45nm after swelling;
[0155] (3) When the graphene oxide membrane material obtained in step (2) is isotropically stretched and steam treated at the same time, 30 mL of plasticizing solvent is first added to the flux pool a, and then the graphene oxide membrane material is fixed between the upper and lower layers of cylinders a by the membrane fixing screw a and the membrane fixing screw a is adjusted to keep the two-dimensional sheet macroscopic assembly membrane taut, and then heated by the heating device a until the plasticizing solvent is vaporized and then kept at 105°C for 12 hours (the vapor pressure stress during the insulation process is 20000 mmHg), and finally the plasticized graphene oxide membrane material is taken out and placed in a vacuum environment at 150°C for low-temperature reduction for 12 hours to obtain a graphene oxide membrane with high separation efficiency and high ion selectivity.
[0156] The final highly efficient separation and high ion selectivity graphene oxide membrane had a tensile strength of 750 MPa, an interlayer spacing of 0.3 nm, a sheet stacking domain height of 12 nm, and a Herman's orientation factor of 0.95; the highly efficient separation and high ion selectivity graphene oxide membrane swelled after being immersed in water for 12 hours, and after swelling, the interlayer spacing of the highly efficient separation and high ion selectivity graphene oxide membrane increased to 0.32 nm.
[0157] Application of high-efficiency separation and high-ion selectivity graphene oxide membrane, using the high-efficiency separation and high-ion selectivity graphene oxide membrane prepared as above as ion separation membrane.
[0158] When the high-efficiency separation and high ion-selective graphene oxide membrane is used as an ion separation membrane, it is known that the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane is 600LMH / bar, the inorganic salt retention rate is 95%, the dye retention rate is 99%, and the divalent / monovalent ion screening selectivity factor is 50; after 120 hours of continuous testing, the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane decreased by 10%.
[0159] Example B6
[0160] The preparation method of graphene oxide membrane with high separation efficiency and high ion selectivity comprises the following steps:
[0161] (1) Preparation of raw materials and equipment used;
[0162] Graphene oxide aqueous solution: the solute is graphene oxide, the flake size of graphene oxide is 15-20 μm, the flake thickness is 10 nm, and the atomic ratio of carbon to oxygen is 4:1;
[0163] The apparatus used for isotropic stretching and steam treatment was the apparatus described in Example A2, wherein n was 4, m was 3, the height of the solvent pool b was 8 cm, the volume was 100 mL, and the angle between the inclined rod II and the central axis of the cylinder b was 102.5°;
[0164] Plasticizing solvent: ethanol;
[0165] (2) Preparation of graphene oxide film materials;
[0166] The concentration is 8 mg g -1 A graphene oxide aqueous solution is prepared, a quartz watch glass is used as a casting substrate, and after casting, it is dried at 45° C. for 12 hours, and after removing the casting substrate, a graphene oxide film material with a thickness of 20 μm is obtained;
[0167] The water permeability of the obtained graphene oxide membrane material is 50LMH / bar, and the mass area density D is 10mg·cm -2 , the interlayer spacing is 0.55nm, the tensile strength is 150MPa, the stacking domain height is 4.9nm, and the Herman's orientation factor is 0.35; the graphene oxide film material swells after being immersed in water for 18h, and the interlayer spacing of the graphene oxide film material increases to 0.64nm after swelling;
[0168] (3) When the graphene oxide membrane material obtained in step (2) is isotropically stretched and steam treated at the same time, 50 mL of plasticizing solvent is first added to the solvent pool b, and then the graphene oxide membrane material is fixed between the upper and lower cylinders b by the membrane fixing screws b and the membrane fixing screws b are adjusted to keep the two-dimensional sheet macro-assembly membrane in a taut state, and then heated by the heating device b until the plasticizing solvent is vaporized, and at the same time, the pressing plate is pressed downward and kept warm at 90°C for 18 hours (the stretching displacement of the two-dimensional sheet macro-assembly membrane after the insulation is completed is 1.5 mm), and finally the plasticized graphene oxide membrane material is taken out and placed in a vacuum environment at 120°C for low-temperature reduction for 18 hours to obtain a high-efficiency separation and high ion selectivity graphene oxide membrane.
[0169] The final highly efficient separation and high ion selectivity graphene oxide membrane had a tensile strength of 300 MPa, an interlayer spacing of 0.36 nm, a sheet stacking domain height of 7.8 nm, and a Herman's orientation factor of 0.59; the highly efficient separation and high ion selectivity graphene oxide membrane swelled after being immersed in water for 18 hours, and after swelling, the interlayer spacing of the highly efficient separation and high ion selectivity graphene oxide membrane increased to 0.38 nm.
[0170] Application of high-efficiency separation and high-ion selectivity graphene oxide membrane, using the high-efficiency separation and high-ion selectivity graphene oxide membrane prepared as above as ion separation membrane.
[0171] When the high-efficiency separation and high ion-selective graphene oxide membrane is used as an ion separation membrane, it is known that the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane is 280LMH / bar, the inorganic salt retention rate is 82%, the dye retention rate is 90%, and the divalent / monovalent ion screening selectivity factor is 36; after 120 hours of continuous testing, the water permeability of the high-efficiency separation and high ion-selective graphene oxide membrane decreased by 15%.
Claims
1. A method for preparing a graphene oxide membrane with high separation efficiency and high ion selectivity, characterized in that: The formed graphene oxide membrane material is isotropically stretched and steam treated at the same time, and then placed in a vacuum environment at 80-150°C for low-temperature reduction to obtain a graphene oxide membrane with high separation efficiency and high ion selectivity. The steam used in the steam treatment is plasticizing steam, which is formed by evaporating a plasticizing solvent having a plasticizing effect on the graphene oxide film material, and the plasticizing solvent is ethanol or isopropanol; When the thickness of the graphene oxide film material is ≤10 μm, the device used for isotropically stretching and steam treating the graphene oxide film material at the same time includes a solvent pool a and a heating device a; the top of the solvent pool a is a vertically arranged cylinder a, the cylinder a is divided into an upper and a lower layer and is detachably connected by 2m film fixing screws a, m>2, and the 2m film fixing screws a are evenly distributed around the circumference of the central axis of the cylinder a; the heating device a is used to heat the solvent pool a; the solvent vapor stress in a closed environment is converted into an isotropic tensile stress after contacting the graphene oxide film material fixed above, thereby realizing isotropic stretching and steam treating the graphene oxide film material at the same time; the amount of the plasticizing solvent is 30~100mL, the insulation temperature after the plasticizing solvent is vaporized is 90~105℃, the generated vapor pressure stress is 1200~20000 mmHg, and the insulation time after the plasticizing solvent is vaporized is 12~24h; When the thickness of the graphene oxide film material is greater than 10 μm, the device used for simultaneously performing isotropic stretching and steam treatment on the graphene oxide film material includes a solvent pool b, a heating device b, a deformable tube and a regulator; the bottom of the deformable tube is sealed and connected to the top of the solvent pool b, the top of the deformable tube is a vertically arranged cylinder b, the cylinder b is divided into an upper and lower layer and is detachably connected by 2m membrane fixing screws b, m>2, and the 2m membrane fixing screws b are evenly distributed around the circumference of the central axis of the cylinder b; the regulator is used to control the radial outward expansion of the cylinder b; the heating device b is used to heat the solvent pool b; the outward extension of the deformable tube is controlled by the regulator, and during the extension of the deformable tube, it produces an epitaxial equibiaxial tensile displacement on the circumferential boundary of the graphene oxide film material in contact with it, and the tensile displacement is 1.5 mm~3 mm, thereby realizing simultaneous isotropic stretching and steam treatment of the graphene oxide film material.
2. The method for preparing a highly efficient separation and highly ion-selective graphene oxide membrane according to claim 1, characterized in that: The thickness of the graphene oxide film material is 10nm~50μm.
3. The method for preparing a graphene oxide membrane with high separation efficiency and high ion selectivity according to claim 2, characterized in that: The regulator includes a displacement bracket, a pressing plate, an upper bracket, a limiting structure and a lower bracket; The displacement bracket is a conical cap-shaped structure with the tip at the top, comprising 2n inclined rods I, n>3, the upper ends of the 2n inclined rods I are simultaneously connected to the center of the lower surface of the pressing plate, and the lower ends are evenly distributed around a point o, the point o is located on the central axis of the pressing plate, and the pressing plate is coaxial with the cylinder b; The upper support includes 2n horizontal rods, which are radially distributed around point o. The two ends of the horizontal rods are respectively marked as end a and end b. End a is closer to point o than end b. The ends a of the 2n horizontal rods are respectively hinged to the lower ends of the 2n oblique rods I in a one-to-one correspondence. The limiting structure restricts the 2n horizontal rods to move only along their own length direction; The b ends of two adjacent horizontal rods are each connected by an arc bar, and at least one set of opposite arc bars is composed of three sections: left, middle and right. The middle section is composed of a separated inner layer and outer layer. The outer layer of the middle section is fixedly connected to the left section, and the inner layer of the middle section is fixedly connected to the right section. All the arc bars form a circular ring, and the circular ring extends vertically downward to form a circular tube. The lower support includes 2n oblique rods II, which are distributed in an umbrella shape around the central axis of the cylinder b. The angle between the oblique rods II and the central axis of the cylinder b is 100-105°. The lower layer of the cylinder b extends radially outward and is connected to the upper ends of the 2n oblique rods II, and the lower ends of the 2n oblique rods II are connected to the circular tube.
4. The method for preparing a highly efficient separation and highly ion-selective graphene oxide membrane according to claim 3, characterized in that: The regulator also includes a height measuring bracket, which is vertically arranged on one side of the pressing plate and fixedly connected to the upper bracket.
5. The method for preparing a graphene oxide membrane with high separation efficiency and high ion selectivity according to claim 1, characterized in that: The forming method of the graphene oxide film material is: vacuum filtering the graphene oxide aqueous solution into a film, spin coating it multiple times into a film, pouring it on a substrate to evaporate and assemble it into a film or continuously scraping it into a film, and then drying and forming it to obtain the graphene oxide film material.
6. The method for preparing a graphene oxide membrane with high separation efficiency and high ion selectivity according to claim 5, characterized in that: The interlayer spacing of the graphene oxide film material is 0.35~0.8nm, the tensile strength is 20~300MPa, the layer stacking domain height is 3~9nm, and the Herman's orientation factor is 0.2~0.5; after the graphene oxide film material swells in water, the interlayer spacing increases to 0.45~1nm.
7. A highly efficient separation and high ion selectivity graphene oxide membrane prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The tensile strength of the high-efficiency separation and high ion selectivity graphene oxide membrane is 50~750MPa, the interlayer spacing is 0.3~0.4nm, the layer stacking domain height is 5~12nm, and the Herman's orientation factor is 0.3~0.95; after the high-efficiency separation and high ion selectivity graphene oxide membrane swells in water, the interlayer spacing increases to 0.32~0.45nm.
8. The use of the highly efficient separation and highly ion-selective graphene oxide membrane according to claim 7, characterized in that: Used as ion separation membrane; The water permeability of the high-efficiency separation and high ion selectivity graphene oxide membrane is 30~600LMH / bar, the inorganic salt retention rate is 70~95%, the dye retention rate is 85~99%, and the divalent / monovalent ion screening selectivity factor is 10~50; after 120 hours of continuous testing, the water permeability of the high-efficiency separation and high ion selectivity graphene oxide membrane decreased by 10~20%.
Citation Information
Patent Citations
Graphene-oxide-modified thermoplastic starch composite material and preparing method thereof
CN106009064A
Flexible carbon film and preparation method thereof
CN106116580A
Method for strengthening graphene oxide membrane and preparation method of high-strength graphene oxide membrane
CN108793149A
Kitchen waste oil -water separation device
CN205095466U